Autonomic regulation in adolescents after rapid ascent to 3454 metres. (22nd September 2015) - Stuber, T; Rimoldi, SF; Lim, PB; Garcin, S; Duplain, H; Bloch, J; Sartori, C; Scherrer, U; Allemann, Y; Peters, NS
Abstract : Increasing numbers of children and adolescents are travelling to destinations situated at high altitude and are subsequently exposed to altitude-related hypoxia and its potential health risks. Rapid ascent to high-altitude triggers sympathetic activation in adults, which can be detected by measurements of heart rate variability (HRV) and contributes when exaggerated to the pathogenesis of high-altitude pulmonary oedema. Data in children on autonomic regulation after rapid ascent to high altitude are lacking. The aim of this study is to characterise autonomic regulation in healthy children and adolescents during short-term exposure to high altitude. 97 healthy children and adolescents (mean ± SD age, 11.9 ± 2.2 years, range 7–17 years, 47 girls and 50 boys) participated in the study. HRV was measured from 5 minutes ECG recording at low altitude (450 m) and 24 h after arriving at the high altitude research station of the Jungfraujoch in Switzerland (3454 m asl). Time domain analysis demonstrated an increase in heart rate in all subjects from low to high altitude (74 ± 9 vs 97 ± 13 bpm, p<0.0001) and a decrease in the standard deviation of normal intervals in all subjects from low to high altitude (7.3 ± 2.3 vs 5.3 ± 2.2, p<0.0001). Frequency domain analysis demonstrated a significant absolute decrease from low to high altitude in total, high and low-frequency powers calculated with linear and non-linear models. In normalised units there was a significant increase of low frequency powers on ascent to high altitude (43.9 ± 17.3 vs 56.9 ± 21.0, p<0.0001). The same was observed with a non-linear (autoregressive) model, in which the amount of low-frequency powers in normalised units increased on ascent to high altitude (51.1 ± 23.3 vs 64.3 ± 20.1, p<0.0001) and the low-frequency/high-frequency ratio increased significantly from low to high altitude (2.04 ± 2.36 vs 4.72 ± 7.10, p = 0.0007). We report here the first study on autonomic regulation in a large group of healthy low-altitude-resident children and adolescents after rapid ascent to high altitude. Children respond similarly to adults with sympathetic activation, an important mechanism in the pathogenesis of high-altitude pulmonary oedema.